2012
DOI: 10.1021/am302285n
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Oligonucleotide and Protein Arrays on Rigid and Flexible Substrates Coated with Reactive Polymer Multilayers

Abstract: We report a top-down approach to the fabrication of oligonucleotide and protein arrays on surfaces coated with ultrathin, amine-reactive polymer multilayers fabricated by the covalent ‘layer-by-layer’ (LbL) assembly of polyethyleneimine (PEI) and the amine-reactive, azlactone-functionalized polymer poly(2-vinyl-4,4-dimethylazlactone) (PVDMA). Manual spotting of amine-terminated oligonucleotide probe sequences on planar glass slides coated with PEI/PVDMA multilayers (~35 nm thick) yielded arrays of immobilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…The signal-to-noise ratios measured here are comparable to those reported for spotted DNA arrays on the same type of substrate. 34 A number of potential applications for RNA arrays, such as the study of RNA binding proteins, aptamers, or the development of new biosensors, depend critically upon minimizing non-specific interactions between the surface and analytes of interest. The ability to synthesize the arrays on a polymeric surface provides an important new avenue for the control of such interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The signal-to-noise ratios measured here are comparable to those reported for spotted DNA arrays on the same type of substrate. 34 A number of potential applications for RNA arrays, such as the study of RNA binding proteins, aptamers, or the development of new biosensors, depend critically upon minimizing non-specific interactions between the surface and analytes of interest. The ability to synthesize the arrays on a polymeric surface provides an important new avenue for the control of such interactions.…”
Section: Resultsmentioning
confidence: 99%
“…355 Covalent LbL assemblies of PEI and the aminereactive, azlactone-functionalized polymer poly(2-vinyl-4,4-dimethylazlactone) were first prepared on planar glass slides, on which amine-terminated oligonucleotide probe sequences had been manually spotted. Hybridization of fluorescently labeled complementary sequences provided fluorescence spots with high signal intensities, high signal-to-noise ratios, and high sequence specificity.…”
Section: ¹1mentioning
confidence: 99%
“…Past studies from our group have demonstrated that interfacial reactions between amine-reactive poly­(2-vinyl-4,4-dimethylazlactone) (PVDMA) and the amine-containing polymer poly­(ethylenimine) (PEI) can drive LbL assembly into films that are either thin, smooth, and relatively featureless at the nanometer scale, or thicker (micrometer-scale) with significant nano- and microscale surface features and substantial nanoscale porosity. These PEI/PVDMA multilayers are potentially useful in at least three ways: (i) similar to other LbL processes, these materials can be fabricated on a broad range of topologically complex substrates, (ii) the assemblies that result exhibit superior stabilities in complex chemical environments owing to the presence of hydrolytically stable amide-based cross-links, and (iii) the resulting films contain residual azlactone groups that can be used to further functionalize and tailor bulk and surface properties by reactions with a range of nucleophiles . These useful properties make PEI/PVDMA multilayers a versatile platform for the elaboration of a broad range of new functional materials, including tailored biointerfaces, , reactive polymer-based capsules, and new types of chemical and biomolecular sensors . More recently, chemically reactive PEI/PVDMA films with substantial degrees of nanoscale roughness and porosity have made possible the design of surface coatings with extreme wetting behaviors (e.g., superhydrophobicity, underwater superoleophobicity, etc.…”
Section: Introductionmentioning
confidence: 99%